2013
DOI: 10.1038/msb.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Efficient translation initiation dictates codon usage at gene start

Abstract: Rare codons are enriched at gene start in many genomes. Genome analysis and experimental testing show that this enrichment evolved to keep the ribosome binding site free from stable mRNA structures, in order to facilitate efficient translation initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
288
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(311 citation statements)
references
References 46 publications
19
288
0
4
Order By: Relevance
“…A genome-wide comparison of the in silico RNA structurome with experimental polysome profiling for allelic variants in hybrid mouse fibroblasts supports these assertions, as alleles with lower in silico-predicted mRNA secondary structure around the transcription start site had greater translation efficiency (defined as the ratio between ribosome-associated mRNA and total mRNA abundance) (37). Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2).…”
Section: Stability and Degradationsupporting
confidence: 82%
“…A genome-wide comparison of the in silico RNA structurome with experimental polysome profiling for allelic variants in hybrid mouse fibroblasts supports these assertions, as alleles with lower in silico-predicted mRNA secondary structure around the transcription start site had greater translation efficiency (defined as the ratio between ribosome-associated mRNA and total mRNA abundance) (37). Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2).…”
Section: Stability and Degradationsupporting
confidence: 82%
“…2) may be supported further by the fine-tuning of the initiation rate via occlusion time due to slow codons [11]: If the translation rates for rare codons are unsaturated, the occlusion time can respond to the changes in the substrate level. Furthermore, secondary mRNA structures near the ribosome binding site is avoided [27] probably because such would reduce the ribosome on-rate, K s [28,29,30]. It is not obvious that slowly translated codons are less likely to form structured mRNA, but altogether it is clear that numerous regards should be solved by the codon usage in the beginning of the mRNA.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…When controlling for the mRNA level, a significant negative correlation was observed between CUB as measured in S. cerevisiae and the absolute translational cis ratio, but not the absolute mRNA cis ratio (analysis of covariance [ANCOVA], P = 1.5 3 10 À12 and 0.13, respectively). The presence of mRNA secondary structure in the vicinity of the start codon has also been implicated in reducing translational efficiency (Kudla et al 2009;Robbins-Pianka et al 2010;Bentele et al 2013;Dvir et al 2013;Goodman et al 2013;Shah et al 2013). We found evidence for a positive correlation between species-specific decreases in computationally predicted secondary structure downstream from the start codon and increased translational efficiency (Supplemental Fig.…”
Section: Evolution At Two Levels Of Gene Expressionmentioning
confidence: 99%